Pore engineering of ultrathin covalent organic framework membranes for organic solvent nanofiltration and molecular sieving - Shinde, Digambar B; Cao, Li; Wonanke, A. D. Dinga; Li, Xiang; Kumar, Sushil; Liu, Xiaowei; Hedhili, Mohamed N; Emwas, Abdul-Hamid; Addicoat, Matthew; Huang, Kuo-Wei; Lai, Zhiping (Chemical science (Cambridge), 2020)
The advantages of two dimensional covalent organic framework membranes to achieve high flux have been demonstrated, but the capability of easy structural modification to manipulate the pore size has not been fully explored yet. Here we report the use of the Langmuir-Blodgett method to synthesize two ultrathin covalent organic framework membranes ( TFP-DPF and TFP-DNF ) that have a similar framework structure to our previously reported covalent organic framework membrane ( TFP-DHF ) but different lengths of carbon chains aiming to rationally control the pore size. The membrane permeation results in the applications of organic solvent nanofiltration and molecular sieving of organic dyes showed a systematic shift of the membrane flux and molecular weight cut-off correlated to the pore size change. These results enhanced our fundamental understanding of transport through uniform channels at nanometer scales. Pore engineering of the covalent organic framework membranes was demonstrated for the first time. Pore surface engineering of ultrathin COF membranes by introducing different lengths of alkyl chains into the skeleton, which allows us to precisely control the pore size of COF membranes for OSN applications and molecular sieving.